Curative anticoagulation prevents endothelial lesion in COVID‐19 patients. (30th July 2020) - Khider, Lina; Gendron, Nicolas; Goudot, Guillaume; Chocron, Richard; Hauw‐Berlemont, Caroline; Cheng, Charles; Rivet, Nadia; Pere, Helene; Roffe, Ariel; Clerc, Sébastien; Lebeaux, David; Debuc, Benjamin; et al.
Abstract: Background: Coronavirus disease‐2019 (COVID‐19) has been associated with cardiovascular complications and coagulation disorders. Objectives: To explore the coagulopathy and endothelial dysfunction in COVID‐19 patients. Methods: The study analyzed clinical and biological profiles of patients with suspected COVID‐19 infection at admission, including hemostasis tests and quantification of circulating endothelial cells (CECs). Results: Among 96 consecutive COVID‐19‐suspected patients fulfilling criteria for hospitalization, 66 were tested positive for SARS‐CoV‐2. COVID‐19‐positive patients were more likely to present with fever ( P  = .02), cough ( P  = .03), and pneumonia at computed tomography (CT) scan ( P  = .002) at admission. Prevalence of D‐dimer >500 ng/mL was higher in COVID‐19‐positive patients (74.2% versus 43.3%; P  = .007). No sign of disseminated intravascular coagulation were identified. Adding D‐dimers >500 ng/mL to gender and pneumonia at CT scan in receiver operating characteristic curve analysis significantly increased area under the curve for COVID‐19 diagnosis. COVID‐19‐positive patients had significantly more CECs at admission ( P  = .008) than COVID‐19‐negative ones. COVID‐19‐positive patients treated with curative anticoagulant prior to admission had fewer CECs ( P  = .02) than those without. Interestingly, patients treated with curative anticoagulation and angiotensin‐converting‐enzyme inhibitors or angiotensin receptor blockers had even fewer CECs ( P  = .007). Conclusion: Curative anticoagulation could prevent COVID‐19‐associated coagulopathy and endothelial lesion.